Prevalence of workplace bullying among medical students: A meta-analysis and systematic review protocol - Hancong Li; Mingchun Mu; Yan He; Jinjin Wang; Zhaolun Cai; Haitao Tang; Bo Zhang; Han Luo; Wen Zeng (PLoS ONE, 2025)
Workplace bullying is a significant issue impacting various professions, including the healthcare sector. This study presents a meta-analysis aimed at assessing the global prevalence of workplace bullying among medical students and identifying potential influencing factors. Previous research suggests that medical students experience higher rates of bullying compared to senior doctors. However, no worldwide meta-analysis has been conducted on this topic. By utilizing a reliable measurement tool, this study will offer a comprehensive analysis of the prevalence of workplace bullying among medical students. The findings are intended to inform the development of strategies to address this issue and enhance the well-being and professional development of medical students worldwide.